Leave me breathless - Dimon, HelenKay (Brava, 2010)
Former FBI agent Callie Robbins takes an assignment to guard ex-GI Joe and judge Bennett Walker, who has been receiving death threats, and, despite his initial negative thoughts about her ability to protect him, the two begin to develop a trusting relationship, which soon turns sexual, while working together to track down the person or people who want him dead.